Drying quality of rubberwood : an industrial perspective. - Ratnasingam, Jegatheswaran; Frieder, Scholz; Rainer, Grohmann (Springer Verlag, 2010)
In this study, the kiln drying yield of 30 mm Rubberwood (Hevea brasiliensis) used for the furniture manufacturing industry in South East Asia was evaluated. The results showed that the average yield loss was 10%, and end-checks, splits and warping were the most common drying defects. It was found that sawn timber from older trees (> 21 years) were less prone to drying defects, and the use of stress relieving treatments significantly reduced the incidence of drying defects.